2017
DOI: 10.1520/jte20150190
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate Gradation Influence on Grouting Results and Mix Design of Asphalt Mixture Skeleton for Semi-Flexible Pavement

Abstract: In this study, to design a satisfactory asphalt mixture skeleton for semi-flexible pavement (SFP), the effects of aggregate gradation on grouting results of porous asphalt mixture were analyzed based on the test results of 22 aggregate gradations. Moreover, the mix design method of asphalt mixture skeleton was also discussed. Results indicated that the grouting effects of asphalt mixture skeleton were affected by its internal void interconnectivity, including the morphological characteristics, structure, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…For example, a given continuous gradation may also contain larger-tier aggregate. The reason may be that the influence of gravel morphology and fine aggregate is overlooked which needs further research [52]. In our opinion, the two viewpoints are all correct, though only the applying scope of these principles is different.…”
Section: Aggregate Gradationmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, a given continuous gradation may also contain larger-tier aggregate. The reason may be that the influence of gravel morphology and fine aggregate is overlooked which needs further research [52]. In our opinion, the two viewpoints are all correct, though only the applying scope of these principles is different.…”
Section: Aggregate Gradationmentioning
confidence: 85%
“…A lower residual void rate of GSP will be obtained after grouting [50,51]. Overall, a coarser aggregate gradation can be more conducive to forming a larger void space, which has better interconnection, to make the grouted cement mortar more easily able to penetrate the OMA mat [46,52]. Subsequently, flexural tensile strength and compressive strength of the following GSP are also be improved, which are positively linked with low-temperature performance and high-temperature performance, respectively [49].…”
Section: Aggregate Gradationmentioning
confidence: 99%
“…It can be seen that the main difference is the nominal size, between 8 to 14 mm, and most of the gradation is single-sized, with very low percentages of fine aggregates, which makes the porous asphalt skeleton. However, the common goal is to achieve the target 25–35% air voids in the mixture, in order to ease the quick infiltration of grouts due to void interconnectivity and high porosity [ 40 , 53 , 54 , 55 ]. Nevertheless, in Malaysian specifications, the nominal size is 20 mm for type-1 and 14 mm for type-2 gradation systems used in the porous asphalt skeleton for semi-flexible pavement surfaces [ 56 ].…”
Section: Factors Influencing the Performance Of Grouts And Semi-flexi...mentioning
confidence: 99%
“…Similarly, another study was conducted by Hou et al, on the random selection of 22 aggregate gradations by varying percentages of coarse aggregates, fine aggregates, and fillers. The effect of grouting on these gradations was evaluated by volumetric analysis, cantabro and binder drainage test as well as wheel tracking and bending tests [42]. It was revealed that grouting ability of OGAM is not only influenced by initial air voids but also on void interconnectivity, morphological characteristics, and size of pores.…”
Section: Selection Of Open Graded Asphalt Mixturementioning
confidence: 99%
“…The fluidity of grouts is usually determined by flow-cone, however, the flow-out time depends on the geometry of the cone. Ordinary Portland cement (OPC), water (different ratios), and/or sand, fillers, and other supplementary cementing materials (such as fly ash and silica fume) Air voids before and after grouting [42].…”
Section: Cement Groutsmentioning
confidence: 99%